2012
DOI: 10.2460/ajvr.73.12.1932
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype of Mycoplasma bovis in beef cattle after arrival at a feedlot

Abstract: The findings implied spread of M bovis among calves and suggested that host factors and copathogens may determine disease outcomes in infected calves. Chronic pulmonary infection with M bovis may represent a dynamic situation of bacterial clearance and reinfection with strains of different AFLP type, rather than continuous infection with a single clone. These findings impact our understanding of why cattle with chronic pneumonia and polyarthritis syndrome inadequately respond to antimicrobial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 27 publications
3
30
0
1
Order By: Relevance
“…haemolytica can be cultured from samples of tracheal air of recently weaned and transported cattle, at levels ranging from 67 to 441 colony-forming units/m 3 , 74 and M. haemolytica is isolated from bronchoalveolar lavage fluid of healthy calves within 2 weeks of arrival to the feedlot but is rare at later times. 25 Paired M. haemolytica isolates from nasal swabs and transtracheal aspirates had the same genotype in 77% of cases (based on pulsed field gel electrophoresis), with significant agreement between the presence and absence of M. haemolytica in these 2 sites. 200 Thus, the presence of M. haemolytica in the nasal cavity likely influences the likelihood of bacteria reaching the lung, although the number of M. haemolytica in the nasal cavity and trachea is not well correlated.…”
Section: Effects Of Predisposing Factors On Bacterial Colonization Ofmentioning
confidence: 96%
See 1 more Smart Citation
“…haemolytica can be cultured from samples of tracheal air of recently weaned and transported cattle, at levels ranging from 67 to 441 colony-forming units/m 3 , 74 and M. haemolytica is isolated from bronchoalveolar lavage fluid of healthy calves within 2 weeks of arrival to the feedlot but is rare at later times. 25 Paired M. haemolytica isolates from nasal swabs and transtracheal aspirates had the same genotype in 77% of cases (based on pulsed field gel electrophoresis), with significant agreement between the presence and absence of M. haemolytica in these 2 sites. 200 Thus, the presence of M. haemolytica in the nasal cavity likely influences the likelihood of bacteria reaching the lung, although the number of M. haemolytica in the nasal cavity and trachea is not well correlated.…”
Section: Effects Of Predisposing Factors On Bacterial Colonization Ofmentioning
confidence: 96%
“…[123][124][125]198 In contrast, generally low titers to Mycoplasma bovis prior to mixing of calf groups suggests that prior exposure is infrequent, and titers have not been correlated with later frequency of disease. 8,25 Maternal antibody is considered important in defense against BRD in the first 3 months of life. Failure to acquire colostral immunoglobulin is associated with an increased prevalence of respiratory disease in this age group and may result from inadequate levels of protective antibodies in colostrum, poor quality or inadequate storage of colostrum, or failure of the neonatal calf to ingest colostrum.…”
Section: Effects Of Predisposing Factors On Antibody Defensesmentioning
confidence: 99%
“…For instance, Multiple Locus Sequence Typing (MLST) has proved suitable for the comparison of isolates collected at an international scale or at a country level because it focuses on sequence analysis of housekeeping genes known to be poorly variable (Bell-Rogers et al, 2012;Manso-Silvan et al, 2012;Register et al, 2014;Rosales et al, 2014;Sulyok et al, 2014). At a breeding area or herd scale, more discriminatory methods have been proposed such as AFLP (Castillo-Alcala et al, 2012;Hendrick et al, 2013;McAuliffe et al, 2004;Soehnlen et al, 2011) or PFGE (Arcangioli et al, 2012;Churchward et al, 2008;Kusiluka et al, 2000;McAuliffe et al, 2004;Pinho et al, 2012;Tola et al, 1999). However these restriction-based methods have to be interpreted with care since they can discriminate single-mutation variants within a clonal population and highlight DNA rearrangements in variable loci (such as the vsp loci) rather than ''true'' genomic differences (Castillo-Alcala et al, 2012;Citti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Natural LRT infections involving M. bovis frequently produce lung lesions characterised by caseonecrotic bronchopneumonia while experimental infections often produce milder lesions (Castillo-Alcala et al, 2012, Caswell andArchambault, 2007). Lung lesions typically have a cranioventral distribution which differs from other forms of bronchopneumonia by the presence of unique multiple coalescing round friable foci of caseous necrosis within the consolidated areas .…”
Section: Mycoplasma Bovis Associated Pneumoniamentioning
confidence: 99%
“…Firstly, the Se of culture is somewhat dependent on the laboratory and the submitted sample (Sachse et al, 1993). Castillo-Alcala et al (2012) found that the culture of fluid samples is more likely to be positive if sediments rather than supernatants are used. The number of viable organisms present in the submitted sample can also affect the culture Se.…”
Section: Bovis Infection (Van Der Merwementioning
confidence: 99%